Development of grammatical and lexical skills in argumentative EFL writing at upper secondary level in Germany and Switzerland - Lötscher, Flavio; Trüb, Ruth; Lohmann, Julian; Möller, Jens; Jansen, Thorben; Keller, Stefan Daniel (Frontiers in Education, 2025)
The ability to write argumentative essays is an important requirement in EFL curricula in Germany and Switzerland, with grammar and lexis serving as indispensable elements of this task. The literature shows that acquiring advanced grammatical and lexical skills is challenging for students, especially genre-specific lexical abilities. In this longitudinal study, we investigate how grammatical and lexical skills develop in two educational systems among learners at upper secondary schools (operationalized as number of grammatical and lexical errors). Based on texts from n = 470 learners at two time points at the beginning and end of Year 11, it shows that learners in both countries made more lexical than grammatical errors (partial η2 = .17). There were no differences between the countries. Longitudinal analyses revealed moderate positive developments in both grammatical and lexical skills over the course of one school year (partial η2 = .08). The study confirms the importance of vocabulary for advanced L2 writers, which seems to pose a larger challenge than grammar and warrants special attention in EFL writing at upper secondary school. Implications for teacher education and classroom practice such as the emulation of model texts are discussed, with a focus on lexical chunks typical of argumentative writing.